Effectiveness of laser welding in cerclage wiring fixation: a biomechanical study - Nachapan Pengrung; Paphon Sa-ngasoongsong; Konlawat Sabsuantang; Nutchanat Thongchuea; Eakkachai Warinsiriruk (Frontiers in Surgery, 2023)
IntroductionCerclage wiring is a common orthopedic procedure for fracture fixation. However, previous studies reported wiring-related perioperative complications, such as wire loosening or breakage, with an incidence rate of up to 77%. Recently, the use of laser welding on medical implants was introduced to connect biomedical materials. This study used laser technology to weld between wires after conventional cerclage fixation. We hypothesized that the laser welding could significantly increase the biomechanical properties of cerclage wiring fixation.Materials and methodsTwenty-five wiring models underwent biomechanical tests in five cerclage wiring configurations (five models per group), namely, (1) single loop, (2) single loop with laser welding, (3) double loop, (4) double loop with one-side laser welding, and (5) double loop with two-side laser welding. Characteristics such as load to failure, mode of failure, and wiring failure were compared between groups. The biocompatibility for a 316L stainless steel wire with laser welding was evaluated via an in vitro hemolysis test.ResultsMean load to failure of the double loop with one-side and two-side laser welding groups were 3,596 ± 346 N and 3,667 ± 240 N, which were significantly higher than for the double-loop group (2,919 ± 717 N) (p = 0.012 and p = 0.044, respectively). Conversely, no significant difference was shown in the comparison of the mean load to failure between the single loop and the single loop with laser-welded cerclage wire (1,251 ± 72 N, 1,352 ± 122 N, and p = 0.12). Untwisted wire and wire breakage were the most common mode of failure. All welding specimens revealed non-hemolytic effects from in vitro hemolysis test.ConclusionLaser welding on cerclage wiring significantly increases the biomechanical property of double cerclage wire fixation. However, further biocompatibility tests and clinical studies are still recommended.